Diary as a Means for a Student to Discover a Country - Chodzkienė, Loreta (Verbum, 2020)
This paper aims to present a diary as a multifaceted means for incoming international students to become familiar with the host country (in this case, Lithuania), discover it through the ways of immersion and exploration, and reflect upon it on the diary pages. Every year the course of ‘Intercultural Communication’ taught at the Institute of Foreign Languages, Faculty of Philology, Vilnius University, welcomes a large number of incoming students from different parts of the world. Further to the subject syllabus, these students are given a special research task: to delve into the context of the host country, focus on a number of socio-cultural aspects, compare and contrast them to the similar ones in their native countries and reflect upon them in their diaries. The paper provides an overview of the accumulated empirical evidence on the attitudinal discoveries of 84 students representing 21 countries. The employed Interpretive content analysis proved to be a flexible and helpful research method to reveal the informants’ existing cultural capital (Bourdieu 1994), to follow the flow of their interpretations consequently leading to the shifts in their attitudes, and thus, contribute to the development of the students’ intercultural communicative competence. This paper sheds light on the informants’ attitudes towards Lithuania as the destination country for their Erasmus+ exchange, as well as their impressions of the academic environment of Vilnius University.